Analysis of the Influencing Factors Associated With Being Designated Alternate Level of Care. (February 2015) - Barnable, Alexia; Welsh, Darlene; Lundrigan, Elaine; Davis, Cynthia
A health care organization within the Western region of Newfoundland and Labrador has been experiencing high levels of alternate level of care (ALC) cases and days within their acute care units. The majority of these individuals are older adults. The overall goal of this mixed-methods study was to identify factors for becoming designated ALC and to present recommendations for early intervention. This research found that older female adults with co-morbid conditions who access emergency medical services often are admitted to a hospital. The authors also found that once these patients are admitted to an acute care unit, they tend to experience functional decline that may also result in being designated ALC. This study outlines recommendations that may prevent patients from being designated ALC.